Predictors of hand hygiene behaviours among primary and secondary school children in a rural district setting in Zimbabwe: a cross-sectional epidemiologic study - Ncube, France; Kanda, Artwell; Chahwanda, Maude; Macherera, Margaret; Ngwenya, Bigboy (Journal of Water, Sanitation and Hygiene for Development, 2020)
Hand hygiene is one of the most effective and efficient ways of controlling faecal–oral diseases. However, little is known about the predictors of hand hygiene behaviours among school children.A predesigned checklist guide was used to observe hygiene behaviours of 460 pupils from four rural schools in Shamva South district, Zimbabwe. A pretested questionnaire was administered to obtain demographic data of the observed school children. Membership of a Water, Sanitation and Hygiene (WASH) club, age, gender and the level of education were associated with hand hygiene practices (p< 0.05). The findings indicated that investing in hand hygiene behaviour change processes among school children using the promotion, formation, resuscitation and empowerment of WASH clubs in schools is important in disease prevention among communities in developing countries. Key words | fingernails, handwashing, hygiene behaviour, hygienic hand drying, sanitation, school children
Keywords: Hand hygiene; Handwashing practices; Hand hygiene behaviour